The Bank Palace in Vlaška Street in Zagreb - Anamarija Topić (Peristil)
The article deals with the palace of the Slavenska banka (Slavic bank) at the intersection of Vlaška and Draškovićeva streets in Zagreb. The palace was designed by architect Hugo Ehrich and built between 1921 and 1923, in the style of interwar classicism. The research is based on preserved archival material, articles from the daily press from the time of construction, construction drawings, old photographs and relevant professional literature. The results of the research provide an insight into the course of construction and equipping of the business and residential building of Slavenska banka.